THE EFFECT OF SUSTAINABILITY REPORTING QUALITY ON FIRM VALUE THE MODERATING ROLE OF AUDIT QUALITY - Andreas Siahaan; Almatius Setya Marsudi (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to empirically examine the effect of sustainability reporting quality on firm value, with audit quality as a moderating variable. The research sample consists of 70 non-financial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period, generating a balanced panel of 350 firm-year observations. The data analysis method uses Robust Least Squares (White cross-section) panel data regression to address the heteroscedasticity problem detected in the initial research model, ensuring unbiased standard errors. The test results show that sustainability reporting quality and audit quality are not proven to have a significant direct effect on firm value. Furthermore, the interaction of audit quality is proven unable to moderate the relationship between sustainability reporting quality and firm value. The insignificance of these findings is indicated by the presence of information asymmetry, materiality bias due to industrial sector heterogeneity, and market expectations that assume audit quality as a basic standard of operational compliance (hygiene factor) rather than a value-adding catalyst. Conversely, the profitability variable (ROA) is proven to consistently have a positive and significant effect on firm value. This study confirms that in assessing equity valuation in the Indonesian capital market, investors still consider historical financial fundamental performance as the most transparent and measurable primary instrument compared to non-financial disclosures. The practical implication suggests that standardizing sustainability assurance by independent third parties is urgently required to mitigate greenwashing risks and enhance the value-relevance of ESG disclosures.